Kajian efek Mpemba pada pendinginan air keran yang awalnya dipanaskan secara infinitesimal - Founda Noviani, Elisabeth Pratidhina; Setiawan, Arif; Dwandaru, Wipsar Sunu Brams (Jurnal Sains Dasar, 2013)
Abstract   The purpose of this research is to know whether in the cooling process of tap water that is initially heated infinitesimally follow the Mpemba effect or not. The sample that is used in this research is tap water from a uniform source. The control variables are freezer temperature, the content of water, volume of water, and type of water. Two variations are done on the sample, i.e. the water is initially heated infinitesimally and the water is not heated. Both samples are cooled together in a freezer. For some period of time their temperature is measured. The experiment is repeated nine times. Based on the analysis, water that is initially heated infinitesimally takes shorter time to reach zero centigrade than water that is initially unheated. The cooling graph of water that is initially heated infinitesimally intersects the cooling graph of water that is initially unheated. The intersection lies between 5.5oC until 26.5o C. From all parameters that are obtained from the data analysis, it can be concluded that the Mpemba effect occurs consistently in the cooling process of tap water that is initially heated infinitesimally.   Key words: Mpemba effect, freezing, tap water, infinitesimal heating, cooling, time